(untitled) (Journal of Fiber Bioengineering and Informatics, 2009)
A direct polymerization process was developed to synthesize homo- and copolymers of L-lactic acid. The properties and structures of the products were characterized by ¹H nuclear magnetic resonance (¹H-NMR). It was found that PLLA can be prepared by direct synthesis using melt polycondensation. Moreover, the number-average molecular weight (Mn) and compositions of each polymer was determined by ¹H-NMR spectra. In the meantime, the ¹H-NMR spectra was also used for racemization analysis..